1998
DOI: 10.1016/s0895-7061(98)00087-9
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal reduction of blood pressure and the antihypertensive response to a diuretic or angiotensin converting enzyme inhibitor in obese hypertensive patients

Abstract: During a 12-week, multicenter study to evaluate the efficacy and safety of lisinopril and hydrochlorothiazide (HCTZ) for the treatment of obesity-related hypertension, ambulatory blood pressure (ABP) monitoring was performed both at baseline and at study completion in 124 patients. Patients were randomized to three groups: placebo, lisinopril (10, 20, or 40 mg/day), or HCTZ (12.5, 25, or 50 mg/day). All groups were matched with regard to sex, race, age, body mass index, and waist/hip ratio. The primary analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 28 publications
1
17
0
3
Order By: Relevance
“…20 These authors also showed that hydrochlorothiazide effectively lowered 24-hour BP in nondippers and blacks, whose elevated salt sensitivity has been previously described. 3,4,9,10,12 In the present study, similar to the previous report, 20 the response to hydrochlorothiazide therapy in nondippers was greater than that in dippers. These findings, together with the present study, indicate that diuretics lower nighttime BP, especially in salt-sensitive hypertensives, and shift the circadian rhythm of BP in these patients from nondipper to dipper.…”
Section: Discussionmentioning
confidence: 63%
“…20 These authors also showed that hydrochlorothiazide effectively lowered 24-hour BP in nondippers and blacks, whose elevated salt sensitivity has been previously described. 3,4,9,10,12 In the present study, similar to the previous report, 20 the response to hydrochlorothiazide therapy in nondippers was greater than that in dippers. These findings, together with the present study, indicate that diuretics lower nighttime BP, especially in salt-sensitive hypertensives, and shift the circadian rhythm of BP in these patients from nondipper to dipper.…”
Section: Discussionmentioning
confidence: 63%
“…Most previous studies that reported race-specific baseline blood pressures (Table 1) had a 2-to 4-mm Hg higher baseline diastolic blood pressure among blacks compared with whites. [11][12][13][14][15][16] Thus, these studies may overestimate the difference in the proportion of whites and blacks achieving a target blood pressure after administration of a specific antihypertensive drug. Many other studies did not report baseline blood pressure separately for whites and blacks (Table 1), thereby making if difficult to interpret their results regarding racial differences in achieving a treatment goal.…”
Section: Discussionmentioning
confidence: 99%
“…If the second evaluation is made after administering a drug, the apparent effect of the drug will be to produce a greater fall of nocturnal BP in the nondippers than in the dippers (as we observed). The best way to exclude this effect is to administer placebo pills to a control group, 23,24 but this may be difficult to perform in the clinical practice setting. Recently, after the recognition of the potential clinical significance of differences in dipping patterns, there have been several studies of the effects of antihypertensive drugs in hypertensive subjects who differ in their nocturnal BP dipping status.…”
Section: Discussionmentioning
confidence: 99%